Serological prevalence of antibodies to SARS-CoV-2 in a prison in the Peruvian Amazon - Rafael-Heredia, Arturo (2022)
Objectives: The objective of this research was to describe the prevalence of antibodies to COVID19 in a prison in Ucayali, Peru. Methods: 325 inmates were selected from the Penitentiary Centerin Pucallpa, Peru through simple random sampling. On 06/25/20 and 07/24/20, the fingerpuncture samples were taken from the inmates for COVID-19, the blood sample was obtainedfor the chemo-luminescent microparticle immunoassay tests. Descriptive statistics were usedfor data analysis with InfoStat software. Results: Of the 325 inmates evaluated, 80 were women(25%) and 245 men (75%), the mean age was 43 years (SD 12.44). Regarding the serologicalresults, 137 (42%) were found with positive IgG and 188 (58%) negative IgG. Regarding positiveIgM 145 (45%) and negative IgM 180 (55%). Regarding the distribution of positive cases by sex,we have 47 women and 141 men with a positive result for IgM or IgG. Conclusion: It is concludedthat there is a high number of inmates who have antibodies against COVID-19.